Answer: a²+b² = -99/2
Step-by-step explanation:
Since we are given two equations, this equations will be solved simultaneously to get a² and b²
a³ - 3ab² = 47 ... 1
b³ - 3a² b = 52... 2
From 1, a(a² - 3b²) = 47...3
From 2, b(b² - 3a²) = 52... 4
Adding 3 and 4, we have;
a²+b²-3b²-3a² = 99 (note that a and b will no longer be part of the equations as they have been factored out)
a²+b²-(3b²+3a²) = 99
(a²+b²) -3(b²+a²)= 99
Taking the difference we have
- 2(a²+b²) = 99
a²+b² = -99/2
Your answer is 5, you use the formula for a pyramid
You can set up two equations from the information given. I will set them up for you:
32 = 4x + 2y
36 = 5x + 2y
Let's solve the first equation to come up with a value for y.
32 = 4x + 2y
32 - 4x = 2y
16 - 2x = y
Now we plug y into the other equation.
36 = 5x + 2(16-2x)
36 = 5x + 32 - 4x
4 = x
Now we have our real x value and we can plug it into the first equation.
32 = 4(4) + 2y
32 = 16 + 2y
16 = 2y
8 = y
Since x = 4 and y = 8, you get the final coordinates of (4,8).
Your answer is the second statement provided above.
-7+(9)=2
you can do the opposite of what is given (9-7)